Validity and Reliability of Indonesian Version of Diabetes Self-Management Questionnaire in Patients with Type 2 Diabetes at Primary Care - Akhmad Azmiardi (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2025)
Introduction: Diabetes self-management is critical for effective diabetes mellitus management. This study aimed to assess the validity and reliability of the Indonesian version of the Diabetes Self-Management Questionnaire (DSMQ) among patients with type 2 diabetes in a primary care setting.Methods:This cross-sectional study was conducted among patients with type 2 diabetes at primary health care facilities in Singkawang City, West Borneo, Indonesia. Data were collected through interviews or face-to-face meetings with 30 patients diagnosed with type 2 diabetes mellitus undergoing outpatient treatment. The selection criteria included: patients aged 20-75 years, not pregnant or breastfeeding, free from complications affecting physical, mental, and emotional states, and willing to participate voluntarily. The DSMQ assesses self-management behaviors through a multidimensional questionnaire rated on a four-point scale. Construct validity was evaluated using Pearson’s r correlation values, and reliability was assessed using Cronbach’s alpha coefficient, with thresholds set at >0.361 and >0.70, respectively.Results:The study population primarily consisted of women (76.7%), with most respondents aged 50 years and older (53.3%) and predominantly married (93.3%). Educational levels were generally low, with 40% having primary education. The DSMQ showed high validity and reliability across its subscales. Pearson’s r values ranged from 0.393 to 0.865, indicating significant correlations. Cronbach’s alpha coefficient for the DSMQ was 0.930, reflecting excellent internal consistency.Conclusions: The Indonesian version of the DSMQ demonstrated strong validity and reliability for assessing diabetes self-management behaviors in patients with type 2 diabetes